2-Hydroxymelatonin Promotes Seed Germination by Increasing Reactive Oxygen Species Production and Gibberellin Synthesis in Arabidopsis thaliana - Hyoung Yool Lee; Kyoungwhan Back (MDPI AG, 2022)
It was recently reported that 2-hydroxymelatonin (2-OHM) is responsible for inducing reactive oxygen species (ROS) in plants. ROS are crucial molecules that promote germination through interaction with hormones such as gibberellic acid (GA). In this study, to confirm the pro-oxidant role of 2-OHM, we investigated its effect on seed germination in Arabidopsis thaliana (L.) Heynh. Columbia-0. We found that 2-OHM treatment stimulated seed germination by 90% and 330% in non-dormant and dormant seeds, respectively, whereas melatonin marginally increased germination (~13%) in both seed types compared to untreated control seeds. The germination promotion effects of exogenous 2-OHM treatment were due to increased ROS production followed by the induction of GA synthesis and expression of responsive genes. Accordingly, melatonin 2-hydroxylase (M2H), the gene responsible for 2-OHM synthesis, was strictly expressed only during the germination process. Further molecular genetic analyses using m2h knockout mutant and M2H overexpression clearly supported an increase in ROS triggered by 2-OHM, followed by increased expression of GA-related genes, which shortened the time to germination. Notably, 2-OHM application to m2h knockout mutant seeds fully recovered germination to levels comparable to that of the wild type, whereas melatonin treatment failed to increase germination. Together, these results indicate that 2-OHM is a pivotal molecule that triggers increased ROS production during seed germination, thereby enhancing germination via the GA pathway in Arabidopsis thaliana.